Development Word Search Puzzle Learning Media as an Effort to Increase Knowledge of Dental Health Maintenance in Junior High School - Levina, Nur; Fadjeri, Indrayati (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: Dental and oral health is an integral part of the overall health of the body. Dental and oral health problems in school children are often caused by bad habits due to lack of knowledge. Counseling is the process of conveying information and understanding that involves various efforts to encourage individuals to maintain dental and oral health. One of the efforts to increase knowledge through counseling is to use simple and interesting learning media such as word search puzzles because it has the potential to increase students' enthusiasm in participating in learning activities. Methods: The method of this research is Research and Development (R&D). The sample using the Random Sampling technique amounted to 58 students. The instruments in this study are Pre-test and Post-test questionnaires. Results: The word search puzzle media was successfully developed, it is known that the average validation results by material experts are 97.4% in the category Worthy of trial, validation by media experts is an average of 95.5% which is in the category Worthy of being tested and student validation of 90.0% is included in the category of feasible to be used in the learning process. The results of the study before being given counseling using word search puzzle learning media were 7 students (12.1%) with good criteria, 22 students (37.9%) with sufficient criteria and 29 students (50.0%) with poor criteria. Meanwhile, after being given counseling, there was an increase, namely 45 students (77.6%) with good criteria, 11 students (19.0%) with sufficient criteria, and 2 students (3.4%) with poor criteria. Conclusion: Students' knowledge increased after being given counseling using word search puzzle learning media.